The effect of antibody against TNF alpha on cytokine response in Jarisch-Herxheimer reactions of louse-borne relapsing fever. - Coxon, R; Fekade, D; Knox, K; Hussein, K; Melka, A; Daniel, A; Griffin, G; Warrell, D (Oxford University Press, 1997)
Severe Jarisch Herxheimer reaction (J-HR) precipitated by antibiotic treatment of louse-borne relapsing fever (LBRF) is associated with a transient, marked rise in circulating tumour necrosis factor alpha (TNF alpha), interleukin 6 (IL-6) and interleukin 8 (IL-8). Ovine polyclonal anti-TNF alpha antibody fragments (Fab) were used in a randomized double blind placebo controlled trial in an attempt to prevent this reaction. Within 4 h after penicillin, in controls (n = 29), a several-fold rise in cytokines occurred, concomitant with a fall in spirochaetes and maximal clinical manifestations of the J-HR. An intravenous infusion of anti-TNF alpha Fab, 30 min before penicillin in 20 patients reduced peak plasma levels of IL-6 and IL-8 (but not IL-1 beta) compared with controls (p = 0.01 and < 0.001, respectively) and the incidence of the J-HR, indicating some neutralization of TNF alpha. An apparent fall in TNF alpha reflected interference of anti-TNF alpha in the immunoassay.